The Influence Of Public Accountability Management Control System Implementation On Employee Performance - Indriyani Permatasari; Gun Gunawan Rachman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to examine the effect of Public Accountability and Management Control System Implementation on Employee Performance at Department of Trade and Industry of Bandung (Dinas Perdagangan dan Perindustrian Kota Bandung). The research adopts a quantitative approach, utilizing survey data collected through questionnaires from 36 respondents selected using simple random sampling, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that Public Accountability and Management Control System Implementation have a positive and significant effect on Employee Performance. The model exhibits strong explanatory power, as indicated by the coefficient of determinations (R²) of 0.758, suggesting that these variables explain a substantial proportion of employee performance. This study provides empirical evidence of the importance of Public Accountability and Management Control System Implementation in improving Employee Performance, and enhancing these aspects is expected to contribute to better organizational effectiveness and public service quality, particularly in public sector institutions.